2011
DOI: 10.4236/sgre.2011.24036
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Metering Infrastructure for Electric Vehicle Charging

Abstract: The widely adoption of Electric Vehicle (EV) has been identified as a major challenge for future development of smart grids. The ever increasing electric vehicle charging further increases the energy demand. This paper reports the development of an Advanced Metering Infrastructure (AMI) as an effective tool to reshape the load profile of EV charging by adopting appropriate demand side management strategy. This paper presents a total solution for EV charging service platform (EVAMI) based on power line and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…These communication technologies can be wireless or over PLC that provides bidirectional communication between the network components. In [21], AMI is employed for the EV charging system, which its efficiency in charging schedule scenarios and dynamic pricing are investigated and they concluded that AMI could reduce energy consumption in peak‐load periods by 36%. In other words, AMI shifts 54% of the peak‐load energy demand to the off‐peak periods and reduce the pressure on the power grid during peak‐load demand periods.…”
Section: Proposed System Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…These communication technologies can be wireless or over PLC that provides bidirectional communication between the network components. In [21], AMI is employed for the EV charging system, which its efficiency in charging schedule scenarios and dynamic pricing are investigated and they concluded that AMI could reduce energy consumption in peak‐load periods by 36%. In other words, AMI shifts 54% of the peak‐load energy demand to the off‐peak periods and reduce the pressure on the power grid during peak‐load demand periods.…”
Section: Proposed System Topologymentioning
confidence: 99%
“…Shao et al [20] proposed a charging control framework for a large number of EVs based on Benders decomposition to minimise operation cost without considering any CO 2 emission factors. In [21], Lam et al report the development of an advanced metering infrastructure (AMI) as an effective tool to reshape the load profile of EV charging by adopting appropriate demand-side management strategy. This paper solely focuses on power line communication (PLC) and demand response and ignores the optimisation of charging or discharging scheduling and stochastic behaviour of EV owners and different types of their EVs.…”
Section: Introductionmentioning
confidence: 99%
“…According to [6], in most of the cases, the distribution grid transfers energy without any kind of control mechanism. In a study done by [3] it was proposed an Advanced Metering Infrastructure (AMI), where it is possible to introduce a charging schedule system to advice the charging mode to avoid the peak consumption. The objective is to reduce the peak consumption, to relocate the EV energy demand to "off peak" consumption and to reshape the load profile.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rapid growth of electric vehicle, associate with less autonomy, impacts definitely in increases of energy demand. The extra energy, demand of EV, can cause the distribution circuit congestion and affects the power quality [3]. However, before to think about the increase and quality of energy, it is necessary to investigate the impact on power system.…”
Section: Introductionmentioning
confidence: 99%
“…Such a distributed structure is comprehensive and worth considering. In addition, the establishment of a reliable communication network can also facilitate transactions between EVs [29,30].…”
Section: Introductionmentioning
confidence: 99%